Visible Light Broadband Achromatic Metalens Based on Variable Height Nanopillar Structures - Yongyang Li; Haiyang Huang; Cong Zhang; Xiangshuo Shang; Yang Liu; Junyan Hu; Dengyu Shan; Naiyun Tang; Wei Li (Photonics)
Metalenses have excellent modulation capabilities in terms of phase, amplitude, and polarization of light, significantly reducing the size and complexity of imaging systems, and showing great application prospects. However, like traditional optical meta-atoms, ordinary metalenses suffer from a significant chromatic aberration problem because it is difficult to design the phase distribution for different wavelengths on a single-layer metalens. To address this, various methods for correcting chromatic aberration in metalenses have been proposed and demonstrated, such as spatial multiplexing, material hybridization, and increasing the cross-sectional diversity of metalens meta-atoms. In this paper, a novel design method is used, which expands the parameter space by increasing the cross-sectional diversity of the metalens meta-atoms to provide the phase required for focusing different wavelengths, combined with particle swarm optimization for phase compensation. The multi-level metalens designed by this method achieves a constant and approximate focal length in the visible wavelength range of λ = 450–650 nm, with a polarization-independent absolute focusing efficiency of about 17%, and a numerical aperture (NA) of 0.31 for a lens diameter of 100 μm. This improves the imaging quality.